Pengaruh Dukungan Sosial Supervisi Dan Budaya Organisasi Terhadap Kinerja Karyawan Fungsional PT. Agronesia Saripetojo Sukabumi - Futri Ayu Kartini; Resa Nurmala; Sopyan Saori (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Agronesia Saripetojo Sukabumi was established in 2002 as a manufacturing company that produces ice in the form of blocks, tubes, and crystals that are often used in the culinary industry. This research is based on the existence of a problem encountered in the performance of employees who are suspected because of the findings on social support supervision and organizational culture applied. The purpose of this problem is to determine the effect of social support supervision and organizational culture on employee performance. The use of the method in this study is by using associative descriptive method with quantitative approach. The population is all functional employees totaling 35 people using saturated sampling. In research analysis techniques using validity, reliability, and multiple linear regression. The Data were obtained through research questionnaires distributed to all samples containing 32 statements using the semantic differential measurement system. The results showed that correlation analysis has a strong and high value. The regression coefficient for social support supervision is 0.344 then the regression coefficient for organizational culture is 0.487. The results of the calculation of the f test, show that fcount is greater than ftable. While the results of the t test showed that tcount is greater than the ttable. So it can be concluded that the variables of social support supervision and organizational culture have a positive and significant influence on employee performance.